Urgensi Kepemimpinan dan Mentalitas Siap Berubah Terhadap Kinerja Pegawai di Musim Pandemi Covid-19 - Dewiana Novitasari; Masduki Asbari (Universitas Tidar, 2020)
This research aims to examine the influence of transformational leadership on employee performance in the Refrigeration and Air Conditioning (RAC) industry employees in Bekasi with a mentality of being ready to change as a mediator. The data were collected through simple random sampling technique and the results of a questionnaire that returned and were valid for 132 samples. The data were processed by the SEM method using SmartPLS 3.0 software. From the results of this research, it is concluded that transformational leadership has no significant effect on employee performance, but transformational leadership has a significant and positive effect on the mentality of being ready to change as a mediator. This research also concludes that a mentality of being ready to change has a significant and positive effect on the relationship between transformational leadership and employee performance. The mentality ready to change in this study serves as a full mediator. This new research proposes a model for building employee performance among RAC industrial employees in Bekasi through the development of transformational leadership practices with a change-ready mentality as a mediating variable. This research can pave the way for developing a ready-to-change mentality in employees in the face of the pace of the fourth industrial revolution.